2021
DOI: 10.32358/rpd.2021.v7.572
|View full text |Cite
|
Sign up to set email alerts
|

The circular economy approach for reducing food waste: a systematic review

Abstract: Purpose: This study performs a systematic review through a global analysis of selected articles on food waste and the Circular Economy in the period between 2011 and 2020, indexed in the Scopus and Web of Science databases. Methodology/Approach: It performs a qualitative analysis of 19 selected articles to identify how the Circular Economy can be used in the strategy to reduce food waste. Findings: The main focus is to avoid a global collapse, provoked by the unrestrained increase in production and consumption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
(55 reference statements)
0
3
0
4
Order By: Relevance
“…Gomes et al [41] revealed that consumers who prioritize environmental impact are more inclined to participate in circular consumption practices. Borrello et al [42], Duarte et al [43], Hebrok and Boks [44], and Aschemann-Witzel et al [45] also emphasized the vital role that consumers play in reducing waste and promoting circular behavior. Therefore, it can be stated that consumers' environmental concerns directly shape their level of engagement with circular consumption practices.…”
Section: Collect Information About Environmental Resources In Circula...mentioning
confidence: 99%
“…Gomes et al [41] revealed that consumers who prioritize environmental impact are more inclined to participate in circular consumption practices. Borrello et al [42], Duarte et al [43], Hebrok and Boks [44], and Aschemann-Witzel et al [45] also emphasized the vital role that consumers play in reducing waste and promoting circular behavior. Therefore, it can be stated that consumers' environmental concerns directly shape their level of engagement with circular consumption practices.…”
Section: Collect Information About Environmental Resources In Circula...mentioning
confidence: 99%
“…O método utilizado é a bibliometria, que fornece estatísticas sobre os metadados das publicações de periódicos indicando tendências e relevância quanto a autores, periódicos e artigos (Oliveira et al, 2021;Anand et al, 2021). O periódico como veículo de divulgação científica registrada nos metadados que permitem reconhecer sobre o perfil das pesquisas desenvolvidas em uma área de conhecimento (Cochrane & Mello, 2020;Santos Germano et al, 2021;Silva Duarte, 2021).…”
Section: Metodologiaunclassified
“…O presente estudo tem o objetivo de analisar as contribuições do hackathon como um instrumento para a inovação em redes colaborativas. Para tanto, é feito uso da bibliometria para mapear e investigar a produção científica em periódicos (Nagendrababu et al, 2022), dado que o periódico é o principal veículo de divulgação científica e um estudo de seus metadados pode destacar o valor teórico e prático de um campo de pesquisa (Cochrane & Mello, 2020;Germano, Mello, & Motta., 2021;Duarte et al, 2021).…”
Section: Métodounclassified